Fiscal Policy Impact on Performance of Electronic Commerce Companies in Nigeria - Bessong, Peter K; Esikot, dorenyin Francis; Kankpan, Kechi; Esemi, Sunday (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
The study examined the degree of impact of tax policy on the performance of electronic commerce companies in Nigeria. The study data were sourced from selected electronic commerce firms and government agencies in Nigeria using stratified simple random sampling technique. Regression analysis was used to determine the effect of fiscal policy on the performance of electronic commerce companies in Nigeria. The findings revealed that a change in fiscal policy variables resulted in a proportionate change in the performance of electronic commerce companies in Nigeria. It was concluded that Nigeria current fiscal policy is not comprehensive enough to support digital economic trends like electronic commerce. The lack of established electronic commerce regulating agency is also consequential to an inefficient electronic commerce sector in Nigeria. The study recommended a review of Nigeria’s fiscal policy as it affects contemporary-online businesses like electronic commerce and the development of an all-inclusive-contemporary fiscal policy system that will positively enhance the benefits of electronic commerce business in Nigeria by the Nigeria government. The study further recommended the establishment of a government agency charged with the responsibilities of ensuring the implementation of the reviewed fiscal policy, infrastructural development, and budget monitoring and reporting for capital development projects meant to facilitate the efficiency of electronic commerce business in Nigeria.